(untitled) (Experimental biology, 2009)
In the result of researches established that at digitalis lanata Ehrh woolly seed efficiency depends on weather conditions of a season in which seeds were formed, quantities generatisch runaways, and also from position of boxes in an inflorescence and quantity and weight of seeds in them.